Viabilidade econômica da criação de matrizes e reprodutores de Caiman latirostris no estado de são paulo - Carreira, Laura Borelli Thomaz [UNESP]; Sabbag, Omar Jorge [UNESP]; Abe, Augusto Shinya [UNESP] (My University, 2015)
The breeding of crocodilians has great economic potential. The present study investigated the economic feasibility of crocodilians in the state of São Paulo in different scenarios (sale 40-100 animals per year), with the goal of producing matrices and reproducers for renewal or formation of breeding in other creations, through a sensitivity and stochastic analysis (Monte Carlo simulation). The results of the sensitivity analysis show favorability of this activity in a 15-year horizon, with a Net Present Value (NPV) of R$-202,804.18. However, the projection of variables for a risk analysis (stochastic) enabled the survival of the crocodilian farm without major changes and lower costs for farmers, revealing a low-risk activity, indicating a high probability of economic return.
Economic viability of Caiman latirostris in the state of são paulo (Brazil): Sale of matrices and reproducers
Keywords: Crocodilians; Monte Carlo simulation; Risk analysis